New Oriental genus in the tribe Caliscelini (Hemiptera: Fulgoromorpha: Caliscelidae) from Pakistan - Sohail, Kamran; Usman, Muhammad; Naveed, Hassan; Zhang, Yalin (Zootaxa, 2019)
Formibelle gen. nov. is described based on the type species Formibelle vladimiri sp. nov. from Swat, Pakistan. This new genus represents the second species in the family Caliscelidae from Pakistan. A key to the known genera of Caliscelidae in Pakistan is provided.